2018
DOI: 10.5811/westjem.2017.10.35284
|View full text |Cite
|
Sign up to set email alerts
|

Filling the Gap: Simulation-based Crisis Resource Management Training for Emergency Medicine Residents

Abstract: IntroductionIn today’s team-oriented healthcare environment, high-quality patient care requires physicians to possess not only medical knowledge and technical skills but also crisis resource management (CRM) skills. In emergency medicine (EM), the high acuity and dynamic environment makes CRM skills of physicians particularly critical to healthcare team success. The Accreditation Council of Graduate Medicine Education Core Competencies that guide residency program curriculums include CRM skills; however, EM re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 25 publications
0
21
0
4
Order By: Relevance
“…The assumption that training and assessment increases NTSs is reasonable based on documented experience [ 28 , 29 , 37 , 38 ] and relevant literature [ 6 , 11 , 24 , 25 , 30 ]. However, direct evidence of improved outcomes or reduced amount of errors as results of training in and assessment of NTSs is sparse in the prehospital domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption that training and assessment increases NTSs is reasonable based on documented experience [ 28 , 29 , 37 , 38 ] and relevant literature [ 6 , 11 , 24 , 25 , 30 ]. However, direct evidence of improved outcomes or reduced amount of errors as results of training in and assessment of NTSs is sparse in the prehospital domain.…”
Section: Discussionmentioning
confidence: 99%
“…However, experience from other domains is promising [ 26 , 27 ]. Simulations performed by emergency medicine residents improved leadership, communication, teamwork and situation awareness [ 28 ]. Assessment of a simulation increases learning, thus potentially preventing the repetition of incorrect behaviour [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parsons, et al [15] in their study involving Simulation-based Crisis Resource Management Training for Emergency Medicine Residents reported similar findings. In their study, the researchers observed that the medical residents after their simulated training course displayed improved skills in leadership, problem solving, communication, situational awareness, teamwork, resource utilization.…”
Section: Discussionmentioning
confidence: 67%
“…For these reasons, new, low-cost approaches are required in the practical training of medical students. 19 Parsons et al 20 demonstrated the use of low-cost simulations in the development of emergency crisis management skills, proving that the method is effective in the teaching process and that observational learning in the simulations is able to minimize the time and resources required.…”
Section: Realistic Simulation Associated With Emergency Ultrasoundmentioning
confidence: 99%